2014
DOI: 10.12659/ajcr.891290
|View full text |Cite
|
Sign up to set email alerts
|

Storiform-Pleomorphic Type of Multifocal Malignant Fibrous Histiocytoma of the Lumbar Spine

Abstract: Patient: Male, 67Final Diagnosis: Malignant fibrous histiocytomaSymptoms: Back pain • leg weakness • weight lossMedication: —Clinical Procedure: —Specialty: —Objective:Rare diseaseBackground:We present the extremely rare case of a 67-year-old male with malignant fibrous histiocytoma, arising in the lumbar spine, demonstrated with radiological and pathological studies.Case Report:The patient and his relatives refused open surgical approach and we performed transpedicular vertebral corpus biopsy and vertebroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although pleomorphic and conventional leiomyosarcomatous areas are typically intermixed within a tumor, the demarcation may be distinct or gradual in some cases 14 . Furthermore, it has been reported that PLMS contain myxoid or focally collagenous stroma, which resemble those of storiform-pleomorphic undifferentiated sarcomas 15 . The characteristics of the PDX in our model were closely comparable to the typical characteristics of PLMS, thereby confirming the establishment of an original tumor-like PLMS PDX model.…”
Section: Discussionmentioning
confidence: 99%
“…Although pleomorphic and conventional leiomyosarcomatous areas are typically intermixed within a tumor, the demarcation may be distinct or gradual in some cases 14 . Furthermore, it has been reported that PLMS contain myxoid or focally collagenous stroma, which resemble those of storiform-pleomorphic undifferentiated sarcomas 15 . The characteristics of the PDX in our model were closely comparable to the typical characteristics of PLMS, thereby confirming the establishment of an original tumor-like PLMS PDX model.…”
Section: Discussionmentioning
confidence: 99%